2018
DOI: 10.18273/revuin.v17n2-2018002
|View full text |Cite
|
Sign up to set email alerts
|

Estimación sectorial de la huella hídrica de la ciudad de Bogotá generada en el año 2014

Abstract: Este artículo puede compartirse bajo la licencia CC BY-ND 4.0 y se referencia usando el siguiente formato: A. Castillo-Rodríguez, M. CastroChaparro, A. Gutiérrez-Malaxechebarría, C. Aldana-Gaviria, "Estimación sectorial de la huella hídrica de la ciudad Vol. 17, no. 2, pp. 19-32, 2018 Revista UIS Ingenierías RESUMENEl presente artículo tiene como propósito presentar la estimación de la Huella Hídrica de la ciudad de Bogotá generada en el año 2014. La huella se define, de manera simplificada, como un indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…On the other hand, the Water Footprint Network (WFN) was used in two (2) studies to 12 estimate the water footprint in the domestic sector, focusing on evaluating both the 'Virtual Water' (VW) and the 'Water Footprint' (WF) and, at the same time, determining the blue water footprint (Zhang et al, 2022;Castilla et al, 2018). WFN provides world-class, fully opensource interactive tools that provide essential data and insights into water use.…”
Section: Content Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the Water Footprint Network (WFN) was used in two (2) studies to 12 estimate the water footprint in the domestic sector, focusing on evaluating both the 'Virtual Water' (VW) and the 'Water Footprint' (WF) and, at the same time, determining the blue water footprint (Zhang et al, 2022;Castilla et al, 2018). WFN provides world-class, fully opensource interactive tools that provide essential data and insights into water use.…”
Section: Content Resultsmentioning
confidence: 99%
“…It is therefore suggested that national or regional policies be put in place to incorporate the cost of water into the price of rice products and thereby improve water efficiency. It is estimated that approximately 207.9 m³ of water is consumed for rice, using 90.7 m³ of surface or groundwater (Trujillo et al, 2022;Su, Zheng & Llao, 2022;Gomez et al, 2022;Yu et al, 2022;Wu, Wang & Avishek, 2021;Castilla et al, 2018).…”
Section: Content Resultsmentioning
confidence: 99%
“…Compared to the foreign urban WF, in terms of both the WFprod and the WFcons calculated by Cai et al (2019), China's urban per capita WF was obviously lower than that of US cities (Chini et al, 2017) and higher than that of cities in Egypt and Colombia (Wahba et al, 2018;Castilla et al, 2018). The results of Hoekstra and Chapagain (2006) As shown, the urban WF is influenced by a combination of the urban environment, socioeconomic status, governance and technology (Figure 9a).…”
Section: Comparison Between Production-based Versus Consumption-based Wfmentioning
confidence: 92%
“…Thus, this study can help researchers and decision-makers in similar contexts to carry out WF studies that help identify strategies to reduce pressure on water resources according to socioeconomic conditions. Greater adoption of this methodology in these contexts facilitates understanding the interaction between social relations and economic and natural resources and would improve water management, as in developed countries [72].…”
Section: Principal Component Analysis Of Water Footprintsmentioning
confidence: 99%